PERLINDUNGAN HUKUM BAGI PEMBELI ATAS PERALIHAN HAK ATAS TANAH TERKAIT UANG TITIPAN BPHTB YANG TIDAK DIBAYARKAN OLEH PPAT - Teguh Onoh; Felicitas Sri Marniati; Khalimi; Khalimi Khalimi (Journal of Innovation Research and Knowledge, 2025)
Although the BPHTB (Bea Perolehan Hak atas Tanah dan Bangunan) collection system adheres to the self-assessment mechanism, in which taxpayers calculate and pay their own tax obligations, the Land Deed Official (Pejabat Pembuat Akta Tanah or PPAT) bears the responsibility to ensure that the BPHTB has been fully paid before the deed of transfer of rights is signed. In practice, however, there are cases in which the PPAT fails to remit the BPHTB funds entrusted to them. The research questions in this study are: (1) What is the legal liability of the PPAT for the use of BPHTB entrusted funds that are not paid? and (2) What legal protection is available to the buyer in relation to BPHTB entrusted funds that are not paid by the PPAT? The theories employed in this research are the Theory of Legal Protection as formulated by Satjipto Rahardjo and the Theory of Responsibility as formulated by Hans Kelsen. This study employs a normative juridical method, namely legal research based on literature or secondary data, utilizing primary, secondary, and tertiary legal materials. The research applies several approaches: the statutory approach, case approach, analytical approach, and conceptual approach. Legal materials were collected through the identification and inventory of positive legal rules, books, journals, and other legal sources. The analysis of legal materials was conducted through legal interpretation, specifically grammatical and systematic interpretation, as well as legal construction methods, including analogy construction and the refinement of law (rechtsverfijning). The findings of this research indicate that the legal liability of the PPAT for the use of BPHTB entrusted funds that are not paid encompasses administrative, civil, and criminal aspects. The PPAT is obliged to remit the BPHTB in a timely manner as a prerequisite for the registration of the transfer of land rights, with negligence potentially resulting in administrative sanctions up to dismissal from office, civil liability for damages under Article 1365 or 1239 of the Indonesian Civil Code, and criminal liability for embezzlement or forgery under Articles 372 and 263 of the Indonesian Penal Code. Legal protection for the buyer in such cases includes a statutory interpretation that prioritizes the certainty of rights